If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=-2/3(-1)+6
We simplify the equation to the form, which is simple to understand
y=-2/3(-1)+6
Reorder the terms in parentheses
y=+( + 0.66666666666667)+6
Remove unnecessary parentheses
+y=0.66666666666667+6
We move all terms containing y to the left and all other terms to the right.
+1y=0.66666666666667+6
We simplify left and right side of the equation.
+1y=+6.6666666666667
We divide both sides of the equation by 1 to get y.
y=6.6666666666667
| y=-2/3(1)+6 | | x-6=-8x-6 | | 21+24x=17x+28 | | p+1+6p=4p-14 | | 23x+14y=283 | | 20-3m-1=-4 | | 3x+4(2x+2)=3 | | 4+5x=6+3x | | 4y+8=-26 | | 33+7x+10=13+2x | | 3.5(x+4)+4.5=2(-6.5) | | .66(1+n)=-.50n | | |-3a|=15 | | x^2+10+24= | | y=2/3(-1)-7 | | 9.06=51 | | -62u=60 | | 2y+6=-8 | | (x+4)(x-2)=7 | | y=2/3(1)-7 | | y=2/3(0)-7 | | 6b-38=-6b+14 | | 3(2x+1)=4x-13 | | 54=(4r-5) | | 8(f+8)=1 | | 2a-5(a-4)=-4 | | X+3x-12=180 | | 7=2t-5 | | X(3x-12)=180 | | 4x+(5+2x)=2 | | 5x+18-4=-36 | | x^2+6-30=0 |